(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, it is important to guide students to choose the right profession in the course of education and training, and with the help of the knowledge and skills they have acquired through the lessons organized in the field of technology, no matter which of the professions they choose in their future lives. It is noted that he will become a skilled specialist in any field of his interest. Also, the specific features of the systematic approach to teaching gas processing to students in technology lessons are highlighted.